Effect of pH and nanoclay content on the morphology and physicochemical properties of soy protein/montmorillonite nanocomposite obtained by extrusion. (1st May 2018) - Felix, M.; Martinez, I.; Romero, A.; Partal, P.; Guerrero, A.
Abstract: The present work attempts to clarify the influence of montmorillonite nanoclay content and pH on the mechanical properties of extruded soy protein nanocomposites. The mechanical behaviour is dominated by the formation of positive synergies between protein and nanoclay above a nanoclay concentration threshold. Moreover, the presence of nanoclay can improve water uptake. The pH also exerts a strong influence on mechanical and water absorption properties, although montmorillonite tend to reduce this effect. Eventually, this study put forward the feasibility of using a combination of soy protein and montmorillonite to obtain potentially attractive biodegradable nanocomposite materials, processed by means of a simple and easily scalable twin-screw extruder.